A critical ethical assessment of the South African Termination of Pregnancy Bill - Gcinumkhonto, Danile F. (Danile Favourscent) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2001.